2013
DOI: 10.1002/ejoc.201300176
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Trityl Radicals by Nucleophilic Quenching of Tris(2,3,5,6‐tetrathiaaryl)methyl Cations and Practical and Convenient Large‐Scale Synthesis of Persistent Tris(4‐carboxy‐2,3,5,6‐tetrathiaaryl)methyl Radical

Abstract: Tris(2,3,5,6-tetrathiaaryl)methyl cations, which were generated from the corresponding triarylmethanols in the presence of strong acids, underwent reaction with nucleophiles to give trityl radicals, as the product of a one-electron reduction of the carbocation. Depending on the nature of the nucleophile, the only byproducts were either diamagnetic quinone methides or asymmetrical monosubstituted trityl radicals. Herein, we report a protocol for the large-scale synthesis of the Finland trityl, which has the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 28 publications
2
89
1
Order By: Relevance
“…We prepared tris (8-deutero [1,3]dithiol-4-yl)methanol using D 4 -methanol in place of diethyl carbonate. 33,34 .…”
Section: Macroscopic Simulations and Links To Experimentsmentioning
confidence: 99%
“…We prepared tris (8-deutero [1,3]dithiol-4-yl)methanol using D 4 -methanol in place of diethyl carbonate. 33,34 .…”
Section: Macroscopic Simulations and Links To Experimentsmentioning
confidence: 99%
“…10,40,42 HBF 4 (54 % in Et 2 O, 10 mL, 37.0 mmol) was added to a solution of 1,2,4,5-tetra(tertbutylthio)benzene (1) (16.0 g, 37.2 mmol) in toluene (500 mL). The mixture was stirred for 30 min at RT.…”
Section: General Methods For Synthesismentioning
confidence: 99%
“…Compound 2b (3.49 g, 11.7 mmol), n-BuLi (4.7 mL, 11.7 mmol) and methyl chloroformate (0.3 mL, 3.9 mmol) in dry Tris [8-ethoxycarbonyl-2,2,6,6-tetramethylbenzo [1,2-d:4,5-d']bis( [1,3]dithiole)-4-yl]methanol (4). 23,40 Compound 3a (500 mg, 0.57 mmol) and TMEDA (0.85 mL, 5.7 mmol) were mixed in dry n-hexane (5 mL) under argon atmosphere and cooled to 0 °C. A solution of 2.5 M n-BuLi in hexane (2.3 mL, 5.7 mmol) was added dropwise over 30 min and the mixture was stirred at RT 30 for 3.5 h. Anhydrous toluene (10 mL) was added and the reaction mixture was allowed to stir for an additional 1 h, then added slowly via syringe to cold (-25 °C, cooling bath temperature) diethyl carbonate (3.42 mL, 28.3 mmol) diluted with toluene (5 mL).…”
Section: Tris[2266-( 2 H 3 -Tetramethyl)benzo[12-d:45-d']bis([1mentioning
confidence: 99%
“…In most cases, trityls are not so easy to synthesize, but recently a convenient way of preparing Finland trityl (Rogozhnikova et al, 2013) and diversely substituted trityls were proposed (Scheme 8A), which is based on the quenching of tris(2,3,5,6-tetrathiaaryl)methyl cations by C-, N-, P-, and S-nucleophiles (Scheme 8B) (Tormyshev et al, 2014). The authors found that C-, N-, P-, and S-nucleophiles react with symmetrical tris(2,3,5,6-tetrathiaaryl)methyl cations generated from the corresponding triarylmethanols by strong acids.…”
Section: Synthesis Of Trityl-based Spin Probes and Labelsmentioning
confidence: 99%
“…(B) Synthesis of monofunctional TAMs by nucleophilic quenching of triarylmethyl cation generated from diamagnetic triarylmethanols. (A) Adapted with permission fromRogozhnikova et al (2013).…”
mentioning
confidence: 99%